FORMULASI DAN EVALUASI FISIK SEDIAAN BLUSH ON EKSTRAK UMBI BIT (Beta vulgaris var. rubra (L.) Moq.). SEBAGAI PEWARNA ALAMI - Nichy Eka Putri; Iin Suhesti; Aptika Oktaviana Trisna Dewi (Program Studi D3 Farmasi Politeknik Indonusa Surakarta, 2021)
Beetroot (Beta vulgaris var. Rubra (L.) Moq.). is one of the most useful food ingredients, one of the benefits is to provide a natural color in the manufacture of products. Beetroot contains betasianin, so that the cosmetic formulation of betasianin contained in beetroot produces a red color that can be used as a natural dye for blush. The extraction of betacyanin was carried out by maceration method using 70% ethanol with a ratio of 1: 7. Blush was made into three formulas with different extract concentration variations, namely 25%, 45% and 65%. Each formula was subjected to physical evaluation including organoleptic test, homogeneity test, pH test, adhesion test and preference test. The organoleptic test results of the three formulas had different colors, namely pink to purplish red because the beet root extracts used varied. The results of the pH test in formula 1, formula 2 and formula 3 are 7,10; 6.23 and 5.24 indicate that the first formulation does not meet the good pH requirements, namely 4.5-6.5. The result of adhesion test was 38.5%; 35.6% and 36.7%. The results of the favorite test using SPSS One Way ANOVA in the color category showed that formula 1 was significantly different from formulas 2 and 3, while in the aroma, color and texture categories there was no significant difference between the three blush formulas.